Characterization and anti-aging activities of polysaccharide from Rana dybowskii Guenther - Li, Yiping; Zhao, Xuyan; Wang, Jing; Yu, Qi; Ren, Jing; Jiang, Ziye; Jiao, Lili (Frontiers in Pharmacology, 2024)
Introduction: Rana dybowskii Guenther (RDG), as a traditional Chinese medicine, has been shown to have antioxidant effects. However, studies on the anti-aging effect of RDG are still limited.In this study, we prepared polysaccharides from the skin of RDG (RDGP) by hot water extraction, alcohol precipitation, ion-exchange chromatography and gel chromatography. The proteins were removed using the Sevage method in combination with an enzymatic method. The structural features were analyzed using high-performance gel permeation chromatography, β-elimination reaction and Fourier transform infrared spectra. The anti-aging effect of RDGP was investigated by using D-Gal to establish an aging model in mice, and pathological changes in the hippocampus were observed under a microscope.We obtained the crude polysaccharide DGP from the skin of RDG, with a yield of 61.8%. The free protein was then removed by the Sevage method to obtain DGPI and deproteinated by enzymatic hydrolysis combined with the Sevage method to further remove the bound protein to obtain the high-purity polysaccharide DGPII.Then, DGPIa (1.03×10 5 Da) and DGPIIa (8.42×10 4 Da) were obtained by gel chromatography, monosaccharide composition analysis showed that they were composed of Man, GlcA, GalNAc, Glc, Gal, Fuc with molar ratios of 1: 4.